(1186) the policy of retail price stability سياسة استقرار أسعار التجزئة - sova, vaclav (the institute of national planning, 2018)
economic policy of the socialist state is characterized by effort to maintain the stable level of retail prices. this policy is based not only on economic argument connected with the problem of inflation, but also on extremely serious political factors.